2008
DOI: 10.1016/s0035-9203(08)70025-7
|View full text |Cite
|
Sign up to set email alerts
|

High-level resistance to fluoroquinolones and cephalosporins in Burkholderia pseudomallei and closely related species

Abstract: The molecular mechanisms involved in the development of a high level of resistance to a wide range of antimicrobials in Burkholderia pseudomallei and closely related species have not been sufficiently investigated. In the present study, the properties of B. pseudomallei, B. mallei and B. thailandensis mutants with increased resistance to fluoroquinolones and cephalosporins were analysed. Resistance to pefloxacin, ofloxacin and ceftazidime in B. pseudomallei and B. thailandensis was accompanied by an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
1
25
0
2
Order By: Relevance
“…Our genomic analysis revealed that a Y77S amino acid change in DNA gyrase subunit A (GyrA) is a putative mechanism for this ciprofloxacin resistance. Using stepwise fluoroquinolone selection of B. pseudomallei laboratory mutants, Viktorov and colleagues observed GyrA mutations T83I, G81C, and D87Y in resistant strains (48). Thus, ciprofloxacin resistance in B. pseudomallei is likely encoded by multiple missense gyrA mutations, and here we show that the Y77S mutation may also confer ciprofloxacin resistance, although functional confirmation of its role was not part of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Our genomic analysis revealed that a Y77S amino acid change in DNA gyrase subunit A (GyrA) is a putative mechanism for this ciprofloxacin resistance. Using stepwise fluoroquinolone selection of B. pseudomallei laboratory mutants, Viktorov and colleagues observed GyrA mutations T83I, G81C, and D87Y in resistant strains (48). Thus, ciprofloxacin resistance in B. pseudomallei is likely encoded by multiple missense gyrA mutations, and here we show that the Y77S mutation may also confer ciprofloxacin resistance, although functional confirmation of its role was not part of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli roughly 50% of mutations affect Ser83 (Yoshida et al, 1990). In B. pseudomallei , all in vitro selected fluoroquinolone resistant mutants contained a Thr83Ile mutation (Viktorov et al, 2008). This is consistent with the finding that most Burkholderia species contain a GyrA Thr83 instead of the Ser83 found in other bacteria (Winsor et al, 2008).…”
Section: Burkholderia Pseudomallei Complex Organismsmentioning
confidence: 99%
“…Further investigation of a library of LL-37 fragments with overlapping sequences using Burkholderia thailandensis E264 as a model demonstrated that LL-31, a truncated variant of LL-37 missing the six residues at the C-terminus, displayed the strongest killing effect against B. thailandensis E264 by disrupting the bacterial membrane and subsequent leakage of intracellular components leading to death of the bacterium [13]. Although B. thailandensis is closely related to B. pseudomallei [14], susceptibility to antimicrobial agents differs [15]. Therefore, in the present study, a library of LL-37 fragments was further investigated with B. pseudomallei both in planktonic and biofilm form in comparison with the conventional antibiotic CAZ.…”
Section: Introductionmentioning
confidence: 99%